# 5/6 minus 3/6 as a fraction 5/6 - 3/6 as a fraction provides the detailed information about what is 5/6 minus 3/6 in fraction and decimal form, and the answer with steps to understand how it is being calculated by using different methods.

5/6-3/6 equals to
5/6 - 3/6 = (?)
5/6 - 3/6 = (5 - 3)/6
= 2/6
= (2 x 1)/(2 x 3)
= 1/3
5/6 - 3/6 = 1/3
5/6 minus 3/6 is equal to 1/3

where
5/6 is a fraction as a minuend,
3/6 is a fraction as a subtrahend,
1/3 is the difference between 5/6 and 3/6.

5/6 minus 3/6 as a decimal
5/6 - 3/6 = 1/3
1/3 = 0.3333
5/6-3/6 as a decimal is 0.3333
where
0.3333 is the difference between 5/6 and 3/6.

For values other than 5/6 minus 3/6, use this below tool:

## How-to: 5/6 - 3/6 = ?

The below workout with step by step calculation shows how to find what is 5/6 minus 3/6 in simplest form

Problem and Workout:
What is 5/6 minus 3/6 as a fraction?
step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 5/6
Fraction B: 3/6

What to be found?
5/6-3/6 = ?
Find what's the difference of 5/6 and 3/6.

step 2 Compare the denominators of fractions 5/6 and 3/6 to identify whether it is a like or unlike fraction subtraction. Since the denominators of given fractions 5/6 and 3/6 are equal to each other, it is said to be like fractions subtraction.

step 3 For like fractions subtraction, write the fractions 5/6 and 3/6 in subtraction expression form like the below:
Difference = 5/6 - 3/6

step 4Take the common value 1/6 out from the expression and rewrite the expression like the below:
= 1/6 x (5 /1 - 3 /1)
= 1/6 x (5 - 3)

step 5Simplify the above expression further:
= 1/6 x 2
= 2/6
= 2/6
= 1/3
5/6 - 3/6 = 1/3

Hence,
5/6 minus 3/6 equals to 1/3 